Comparing Mental and Physical Health of Full-Service Sex Workers in the United States to the Health of the General Population in 2019-2020 - Stephen Ramos; Winifred Guerra; Steve Du Bois (Shahid Sadoughi University of Medical Sciences, 2022)
Introduction: Full-service sex workers (FSSWs) are relatively prevalent in the U.S. and are known to face criminalization, stigma, and other factors relating to poor health. The main aim of this study was compare the mental and physical health of full-service sex workers in the United States in 2019-2020 Methods: In this prospective cohort study, participants were recruited through national community samples from U.S.-based FSSW advocacy and community organizations. Data were collected from November 2019 to February 2020. The study sample (n=83) included mostly of the white (81.9%), cisgender females (66.3%), who were relatively young (28.01 [4.25]), and identified as a sexual minority (57.8%). Participants completed an online survey on mental (e.g., depression, anxiety) and physical (e.g., sleep, fatigue) health, using the patient-reported outcomes measurement information system (PROMIS-29). Mean (SD) and Frequency (%) were used for description and for data analysis z-tests in SPSS version 27 with 5% significant level were used. Results: The sample of FSSWs reported significantly poorer health in all health domains compared to the U.S. general population reference indices. FSSWs showed higher levels of depression (p <.001), anxiety (p <.001), fatigue (p <.001), sleep difficulties (p <.001), lower levels of physical functioning (p <.001) and the ability to participate in social activities (p =.03) compared with the U.S. reference indices. Conclusions: FSSWs experience significant mental and physical health disparities compared to general population.  the need for further investigation of the social-ecological determinants of health for members of this marginalized community, many of whom are known to face health inequities.